Recently disclosed chemical entities as potential candidates for management of tuberculosis. (July 2015) - Stec, Jozef; Abourashed, Ehab A
Tuberculosis (TB) is one of the deadliest infectious diseases worldwide. The drug discovery process of novel, safe and effective agents to combat TB involves identification of new molecular targets and novel chemical scaffolds. The current anti-TB drug pipeline includes several small molecules with more to follow as new candidates are disclosed. This review highlights the most significant findings described in 78 international, European and US patents for chemically diverse compounds as prospective anti-TB medications. Main points of emphasis include chemical classification, in vitro and in vivo activity, ADME/Tox profile and mycobacterial target as described in each patent. The collective mass of compounds disclosed in the reviewed patents introduces new candidates as potential therapeutic agents for TB infections.